Synthesis, characterization, and reactivity of a high-spin iron(II) hydrido complex supported by a PNP pincer ligand and its application as a homogenous catalyst for the hydrogenation of alkenes - Ott, Jonas C.; Blasius, Clemens K.; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2018)
This study focused on the synthesis and characterization of a range of low-valent, high-spin iron(II) complexes supported by a carbazole-based PNP pincer-type ligand. The addition of the lithiated ligand (PNP)Li to FeCl2(THF)1.5 yielded the chlorido complex (PNP)FeCl (1), which could be readily converted to the four-coordinate iron(II) alkyl complexes (PNP)FeR [R = CH2SiMe3 (3a), Me (3b), CH2Ph (3c)]. These iron(II) complexes were fully characterized by X-ray analysis and a comprehensive, density-functional-theory-assisted study with complete assignment of their paramagnetic 1H and 13C NMR spectra. Treatment of 1 with KHBEt3 or the addition of molecular hydrogen to (PNP)FeR afforded a high-spin iron(II) PNP hydrido complex, which was identified as the dimer [(PNP)Fe(μ-H)]2 (4) with two bridging hydrido ligands between the iron centers. Exposing complexes 1 and 4 to carbon monoxide led to the corresponding six-coordinate, diamagnetic complexes (PNP)Fe(CO)2Cl (2) and (PNP)Fe(CO)2H (5), of which 2 was present as cis/trans isomers. Furthermore, 4 was found to be an active catalyst for the hydrogenation of alkenes.
Gesehen am 12.03.2020